Humoral and cellular SARS-CoV-2 vaccine responses in patients with giant cell arteritis and polymyalgia rheumatica - Elisabeth Brouwer; Kornelis S M van der Geest; Maria Sandovici; Yannick van Sleen; Janneke H Terpstra; Marieke van der Heiden; Debbie van Baarle; Rosanne D Reitsema; Idil Esen; Elisabeth Raveling-Eelsing; Thomas Lieber; Annemarie M Buisman (RMD Open)
Objectives Giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) are overlapping autoinflammatory diseases affecting people over 50 years. The diseases are treated with immunosuppressive drugs such as prednisolone, methotrexate, leflunomide and tocilizumab. In this study, we assessed the immunogenicity and safety of SARS-CoV-2 vaccinations in these diseases (based on humoral and cellular immunity).Methods Patients (n=45 GCA, n=33 PMR) visited the outpatient clinic twice: pre-vaccination and 4 weeks after the second dose (BNT162b2 or ChAdOx1 vaccine). Patients with previous SARS-CoV-2 infection were excluded. In both pre-vaccination and post-vaccination samples, anti-Spike antibody concentrations were assessed and compared with age-, sex- and vaccine-matched control groups (n=98). In addition, the frequency of SARS-CoV-2 Spike-specific T-cells was assessed by IFN-γ ELIspot assay, and side effects and disease activity were recorded.Results GCA/PMR patients did not have reduced antibody concentrations compared with controls. However, linear regression analysis revealed a significant association of methotrexate and >10 mg/day prednisolone use with lower antibody concentrations in GCA/PMR patients. Evidence of cellular immunity, as assessed by ELIspot assay, was found in 67% of GCA/PMR patients. Patients using >10 mg/day prednisolone had reduced cellular immunity. Importantly, vaccination did not lead to significant side effects or changes in disease activity.Conclusions SARS-CoV-2 vaccination was safe for GCA/PMR patients and immunogenicity was comparable to other older individuals. However, patients using methotrexate and particularly >10 mg/day prednisolone did show lower vaccine responses, which corroborates findings in other autoinflammatory patient populations. These patients may therefore be at higher risk of (potentially even severe) breakthrough SARS-CoV-2 infection.